RNA-binding proteins as a common ground for neurodegeneration and inflammation in amyotrophic lateral sclerosis and multiple sclerosis - Acosta-Galeana, Isabel; Hernández-Martínez, Ricardo; Reyes-Cruz, Tania; Chiquete, Erwin; Aceves-Buendia, Jose de Jesus (Frontiers in Molecular Neuroscience, 2023)
The neurodegenerative and inflammatory illnesses of amyotrophic lateral sclerosis and multiple sclerosis were once thought to be completely distinct entities that did not share any remarkable features, but new research is beginning to reveal more information about their similarities and differences. Here, we review some of the pathophysiological features of both diseases and their experimental models: RNA-binding proteins, energy balance, protein transportation, and protein degradation at the molecular level. We make a thorough analysis on TDP-43 and hnRNP A1 dysfunction, as a possible common ground in both pathologies, establishing a potential link between neurodegeneration and pathological immunity. Furthermore, we highlight the putative variations that diverge from a common ground in an atemporal course that proposes three phases for all relevant molecular events.